Insight into the emerging insect to human pathogen Photorhabdus revealing geographic differences in immune cell tropism - Addison, Max; Hapeshi, Alexia; Wong, Zi Xin; Connolly, John E.; Waterfield, Nicholas Robin (Frontiers in Microbiology, 2024)
Background: Photorhabdus asymbiotica is a species of the insect pathogenic Photorhabdus genus that has been isolated as an etiological agent in human infections. Since then, multiple isolates have been identified worldwide, however actual clinical infections have so far only been identified in North America, Australia and Nepal. Previous research on the clinical isolates had shown that the strains differed in their behaviour when infecting cultured human cells. Methods: In this study we investigate the differences between the pathogenic activities of P. asymbiotica isolates from different geographic locations. Pathogenicity was analysed using infection assays with both cultured cell lines (THP-1, CHO and HEK cells) and primary immune cells, Peripheral Blood Mononuclear cells (PBMCs) isolated from human blood. Results: Here we present findings from the Australian (Kingscliff) and North American (ATCC43949) clinical isolates, and non-clinical soil borne nematode isolates from Thailand (PB68) and Northern Europe (HIT and JUN) of P. asymbiotica. We also show the first findings from a new clinical isolate of P. luminescens (Texas), the first non-asymbiotica species to cause a human infection, confirming its ability to infect and survive inside human immune cells. Conclusions: Here for the first time, we show how P. asymbiotica, selectively infects certain immune cells while avoiding others, and that infectivity varies depending on growth temperature. We also show that the tropism varies depending on the geographical location a strain is isolated from, with only the European HIT and JUN strains lack the ability to survive within mammalian cells in tissue culture.